Gambaran Profil Minat Belajar Siswa (Interest In Learning) Di Sma Negeri 16 Samarinda - Andriyani, Ria Yunita; Prasetya, Akhmad Fajar; Kumara, Agus Ria (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to determine the profile of learning interest among tenth-grade students at SMA Negeri 16 Samarinda. The main focus of this research is to examine the level of students’ learning interest, which is classified into three categories: high, medium, and low. Learning interest is an intrinsic motivation that encourages individuals to be actively involved in the learning process and contributes to the improvement of learning outcomes and academic achievement. The data in this study were obtained from 55 tenth-grade students of SMA Negeri 16 Samarinda. The data collection strategy was carried out through the distribution of a learning interest scale. Based on the results of the scale distribution, it can be concluded that 21 students have a high level of learning interest, 25 students have a moderate level of learning interest, and 9 students have a low level of learning interest. Overall, the students’ learning interest can be categorized as fairly good, as 38% of students fall into the high category, 45% into the medium category, and 16% into the low category.